Effect of Modified Atmosphere Packaging under Ice Cooling on the Postharvest Storage Life and Quality of Spinach (Spinacea oleracea L) Leaves - Mathooko, Francis, M; Vilane, Bruce Roy (Africa Jounals Online, 2003)
The effect of the use of modified atmosphere packaging (MAP) in combination with ice cooling on postharvest storage life (6 days) and market quality attributes of spinach (Spinacea oleracea L.) leaves were investigated. Crates containing the leaves were stored at ambient conditions (temperature 23.7 ± 0.5°C and relative humidity 75 ± 4%) to simulate market conditions. Leaves were evaluated during storage for changes in weight loss, moisture content, quality and wilting condition (based on sensory characteristics), chlorophyll, soluble protein and ascorbic acid contents. Modified atmosphere packaging plus ice cooling reduced moisture loss (0.6% compared to 5% in MAP under ambient conditions), wilting and prolonged market quality of the leaves. In addition, this treatment reduced loss of ascorbic acid and soluble protein (10% compared to 30% under ambient conditions). Modified atmosphere packaging plus ice cooling did not have any added advantage in terms of weight loss and chlorophyll degradation compared to control samples held under MAP at ambient temperature and the treatments were not significantly different (p<0.05). These results indicate that a combination of MAP and ice cooling can considerably extend the postharvest storage life of spinach leaves as well as retaining their market quality attributes. We recommend that farmers and/or traders who transport or handle bulk leafy vegetables to adopt such a method since it has the potential of extending and maintaining product quality.